Social theory and religion - Beckford, James A. (Cambridge University Press, 2003)
This book looks at ways of improving our understanding of religious change by strengthening the links between social theory and the social scientific study of religion. James Beckford reviews the current state of social scientific knowledge about religion. He clarifies the social processes involved in constructing religious and non-religious environments in public and private life. Beckford reveals the importance of these boundaries by referring to studies of secularization, religious diversity, globalization, religious movements and self-identity